1979
DOI: 10.1111/j.1365-2044.1979.tb06246.x
|View full text |Cite
|
Sign up to set email alerts
|

The extension of labour epidural analgesia for Caesarean section

Abstract: Despite the increasing popularity of epidural analgesia in obstetrics, most Caesarean sections in the United Kingdom are still performed under general anaesthesia.' Where epidural analgesia has been established to provide pain relief in labour, extension of the block for Caesarean section is usually possible and can avoid the necessity for general anaesthesia. This paper reports the outcome of applying this policy in 722 consecutive cases. MethodThe implications of epidural analgesia for Caesarean section were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…[18][19][20] At that time, this novel management strategy was particularly important considering that maternal mortality directly related to anesthesia was reported to be 36/100,000 CD. The vast majority were related to the complications of GA. 2 In a follow-up review in 1979, Milne et al 15 described the anesthetic management of 722 consecutive cases of an intrapartum CD and reported an overall 69% (533/772) success rate of conversion of ELA to ESA. At that time, unfortunately, 23.2% (168/772) of the women with ELA underwent GA with no attempt to utilize the in situ epidural catheter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[18][19][20] At that time, this novel management strategy was particularly important considering that maternal mortality directly related to anesthesia was reported to be 36/100,000 CD. The vast majority were related to the complications of GA. 2 In a follow-up review in 1979, Milne et al 15 described the anesthetic management of 722 consecutive cases of an intrapartum CD and reported an overall 69% (533/772) success rate of conversion of ELA to ESA. At that time, unfortunately, 23.2% (168/772) of the women with ELA underwent GA with no attempt to utilize the in situ epidural catheter.…”
Section: Discussionmentioning
confidence: 99%
“…Over the three decades following the initial report by Milne et al, 17 several studies [6][7][8][9][10][11][12][13][14][15] described retrospective reviews of the anesthesia for intrapartum CD in parturients receiving ELA. Unfortunately, when the attempted conversion resulted in inadequate ESA, none of these studies focused on the anesthetic management in an attempt to identify interventions to potentially reduce the need for GA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If adverse effects on the fetus are to be minimised, the analgesic block in labour must be converted rapidly to one adequate for Caesarean section. Milne and colleagues considered that fetal distress was a contraindication to extending pre-existing block [9], but it has been demonstrated that general anaesthesia places the mother at increased risk [5] without always decreasing the time to delivery [ 101. The establishment of epidural analgesia has been recommended in those at risk of requiring Caesarean section since it decreases time to surgery [lo].…”
Section: Discussionmentioning
confidence: 99%
“…Surgery was significantly delayed in those patients (group 2) who required an additional top-up (Table 1). This further delay Thoracic dermatornal level R L R L Pre top-up 9 8 9 9…”
Section: Discussionmentioning
confidence: 99%